Activation Energy of Water and Cryoprotectant Molecules Penetration Through Plasma Membrane of Murine Enterocytes and Dynamics of Their Dehydration During Freezing - Ogurtsova, Viktoriia V.; Kovalenko, Svetlana Ye.; Kovalenko, Igor F.; Gordienko, Olga. I. (Problems of Cryobiology and Cryomedicine, 2017)
In the first approximation one could take into account the effect of cooling on cell membrane permeability and, consequently, the kinetics of a change in cell volume and concentrations of dissolved substances inside it, if the changes in filtration and plasma membrane permeability coefficients for the dissolved solution will comply the Arrhenius law. We determined here the permeability coefficients of murine enterocyte membranes for water molecules and glycerol, 1,2-propanediol (1,2-PD) and dimethyl sulfoxide (DMSO) cryoprotectants at 12Â°C and calculated the values of activation energy of their penetration. There was obtained a time dependence of enterocyte dehydration during cooling with 5, 1, 0.5 and 0.1 deg/min rates. The obtained graphs of enterocyte dehydration indicated the low cooling rates down to 0.1 deg/min to be the most appropriate for using in freezing regimen for thesecells to prevent intracellular crystallization, and 1,2-PD as the most convenient cryoprotectant as compared with glycerol and DMSO, allowing to reach an acceptable level of dehydration even at 0.5 deg/min cooling rate. Assuming the fact, that the survival time of murine enterocytes was also the highest in this cryoprotectant solution unlike glycerol and DMSO, we might conclude 1,2-PD to be the best cryoprotectant among the studied ones to freeze murine enterocytes. Probl Cryobiol Cryomed 2017; 27(3): 242â€“249